Blitz Trump will smash the Left and win - Horowitz, David, 1939- (West Palm Beach, Florida Humanix Books, 2020)
Conservative commentator David Horowitz looks ahead to the 2020 presidential election, chronicling bitter backlash President Trump has faced and denounces left-wing socialist agendas.
Attacks made against Trump have been the most brutal ever mounted against a sitting president of the United States. Blinded by deep-seated hatred of his person and his policies, the Left even desperately tried to oust Trump in a failed impeachment bid. Horowitz shows that their very attacks backfired, turning Trump himself into a near martyrwhile igniting the fervor of his base. With the 2020 election upon us, Trump is going to steamroll this opposition in November using the same playbook he has used to win before. -- adapted from jacket
Preface -- The Trump threat -- Divide, sabotage, resist -- Drain the swamp -- Identity politics -- Make America safe -- Impeachment by any means -- America the ugly -- The terror caucus -- Green communism -- "Equality" versus freedom -- Trump derangement -- Impeachment by hearsay -- What the president actually did -- The MAGA president's war -- Afterword. The nine biggest dangers to America from the anti-Trump Left ; The top ten lies the Democrats have told you.
Includes bibliographical references (pages 215-232) and index.
108269
Keywords: Trump, Donald, -- 1946-; Since 2017; Presidents -- United States -- Election -- 2020 -- Forecasting; Politics and government; United States -- Politics and government -- 2017-